Hesitaton Phenomena in COnversational Interaction Among Speaking EFL Learners (NOBEL: Journal of Literature and Language Teaching, 2020)
Hesitation is the phenomenon when people have speech disfluency in structuring sentences. English Conversation Club is one of the domains where hesitation phenomena occur among EFL learners that practicing their conversation. This study examines the hesitation phenomena and why the members are being hesitated during the interaction. Rose’s theory of taxonomy of hesitation phenomena (2012) is adopted. The approach used is the qualitative approach. Besides, the writer is also the participant observation to collect the data by recording and taking notes. This study resulted that most of the hesitation phenomena are found in the conversation conducted by the learners. The reason for being hesitant is unable to express the language and poor communication skills. Those occur spontaneously and naturally due to the reason that the processing of language in the brain is not as easy as it is produced directly.